Perspectives for Biogas in Europe - van Foreest, F (Oxford Institute for Energy Studies, 2012)
This paper by Floris van Foreest assesses the prospects and challenges facing biomass in the future European energy mix. In studies and discussions of future energy sources the term gas tends to be synonymous with ‘natural gas’ with its attendant issues of upstream exploration and production dynamics, geo-politics and the ubiquitous speculation around shale gas. Biogas is frequently neglected in such a context, despite its potential to contribute to de-carbonisation, in some applications using existing transmission networks. Floris van Foreest describes the present and future conversion processes in which biomass is converted to biogas, the scale and growth of biogas production in individual European countries and the outlook to 2020 and beyond. The technical and economic challenges facing biogas production, its end-use applications and the regulatory and supporting subsidy schemes in force are discussed. While the paper questions whether biogas targets for 2020 will be met, given the current pace of development, it provides the reader with a comprehensive understanding of the subject area and objectively addresses the challenges facing this renewable energy source.